Photooxygenation of 1,2-Diaryltetrahydrobenziimidazole and Crystal Structure of Its Product - Li, Meiying; Shi, Xiaoyan (Asian Journal of Chemistry, 2012)
The reactions of 1-(4-methylsulfonylphenyl)-2-(2,5-chlorophenyl)tetrahydrobenziimidazole (1) with singlet oxygen has been investigated. Compound 1, from a initially formed 2,5-endoperoxide and the subsequence instable zwitterion intermediate, generated a dioxetane. The formed dioxetane through ring-opening and interior-ring electrophilic reaction and finally converted into a more stable seven-membered ring product which has not been reported before. The structure of the photooxygenation product was elucidated by X-ray analysis, H NMR, MS and elemental analysis. The compound 1,2-diaryltetrahydrobenziimidazole crystallizes in monoclinic, space group P2(1)/c with a = 18.533(4) (Å), a = 90(º); b = 7.7658(16) (Å), b = 91.96(3)(º); c = 14.203(3) (Å), g = 90(º); V = 2042.9(7) Å3, Z = 4, F(000) = 948, Dc = 1.474 (g cm-3), C20H18N2O4SCl2, Mr = 453.39 and μ = 0.444 mm-1.